Reforest or perish: ecosystem services provided by riparian vegetation to improve water quality in an urban reservoir (São Paulo, Brazil) - Adas, Mariana Amélia Arantes; Hardt, Elisa; Miraglia, Simone Georges el Khouri; Semensatto, Décio (Sustainability in Debate, 2020)
We estimated the economic value of ecosystem services provided by the legally protected vegetation in riparian zones (RPA- riparian protected areas) of watercourses of the Guarapiranga Reservoir watershed (São Paulo, Brazil), considering two scenarios: (i) the value of ecosystem services provided if the RPA recovery complies with the applicable environmental legislation; and (ii) the year 2030, maintaining the urbanization rate and the loss of vegetation cover in the watershed observed between 1986 and 2010. Accomplishing the first scenario demands reforesting 5,917.5 ha of the RPA, which may reduce the annual expenses with chemicals for water treatment and save USD 181.774 per 1000 m3 of treated water. For 2030, we estimated a loss of 6,220 ha of vegetation cover in the RPA (1986 as the initial reference). The loss of ecosystem services provided by RPA would result in an accumulated increase of about USD 318 million in water treatment costs between 2011 and 2030.